Innovative process to enrich carbon content of EFB-derived biochar as an alternative energy source in ironmaking - Hadi, Purwanto; Rozhan, Alya Naili; Hamzah, Mohd. Salleh (Hindawi Publication, 2018)
This paper describes the mechanism of a developed process—an integrated pyrolysis-tar decomposition process—to produce oil palm empty fruit bunch- (EFB-) derived biochar with additional solid carbon within the biochar bodies, produced by decomposition of tar vapor on its pore surface, using the chemical vapor infiltration (CVI) method. The product, carbon-infiltrated biochar, was characterized to investigate the possibility to be used as partial coke breeze replacement in ironmaking. Carbon-infiltrated biochar is proposed to be utilized for a sintering process that could reduce the consumption of coke and CO2 emission in iron-steel industry.